2017
DOI: 10.1002/ejhf.850
|View full text |Cite
|
Sign up to set email alerts
|

Modalities and Effects of Left Ventricle Unloading on Extracorporeal Life support: a Review of the Current Literature

Abstract: Nowadays, only a few data are available about left heart unloading in V-A ECMO support. Despite the well-known controversy, IABP remains widely used in combination with V-A ECMO. Percutaneous approaches utilizing unloading devices is becoming an increasingly used option. However, further studies are required to establish the optimal LV unloading method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
206
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(216 citation statements)
references
References 49 publications
2
206
1
7
Order By: Relevance
“…This approach often fails in severe myocardial dysfunction, especially in the early phases after ECMO implantation, when unrecovered myocardium may be unresponsive to inotropes. Another way, how to achieve LV unloading, may be by either surgical or less effective percutaneous venting of LV (Meani et al, 2017). Additionally, an indirect LV unloading with intra-aortic balloon pump has been reported with variable success in VA-ECMO patients with partially preserved cardiac contractility (Doll et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach often fails in severe myocardial dysfunction, especially in the early phases after ECMO implantation, when unrecovered myocardium may be unresponsive to inotropes. Another way, how to achieve LV unloading, may be by either surgical or less effective percutaneous venting of LV (Meani et al, 2017). Additionally, an indirect LV unloading with intra-aortic balloon pump has been reported with variable success in VA-ECMO patients with partially preserved cardiac contractility (Doll et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, very promising possibility is adding Impella device that represents an alternative option to support antegrade flow from LV to aorta (Cheng et al, 2013), however it is not routinely available particularly due to its cost. Nevertheless, due to the insufficient data from clinical trials it is not clear which venting method is superior to another and its effect on mortality also remains unknown (Meani et al, 2017). A different approach compared to VA-ECMO is the use of left-ventricular assist device (LVAD) with the drainage cannula implanted directly into the LV, which has also been successfully used in patients with post-cardiotomy heart failure (Mebazaa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of modalities of left ventricular unloading on extracorporeal life support [7], only 16 % of cases are conducted surgically. Certainly, that can be explained by the aggressive character of actual surgical approaches which seem generally not suitable for patients in cardiogenic choc, pulmonary oedema, and anticoagulation therapy.…”
Section: Commentsmentioning
confidence: 99%
“…In the light of these concepts, the usefulness of VA ECMO is still under debate and its efficacy is variable, depending on numerous factors (2).…”
mentioning
confidence: 99%
“…Different techniques have been developed, which can be surgical, percutaneous or using dedicated devices (2). The authors reported their institutional policy to decompress the LV by percutaneous femoral placement of an Impella 2.5 or CP left ventricular assist device (LVAD; Abiomed, Danvers, MA), which was implanted in 13 out of 19 unloaded VA ECMO runs.…”
mentioning
confidence: 99%